Rapid Reduction in Breast Cancer Mortality With Inorganic Arsenic in Drinking Water - Smith, Allan H. (EBioMedicine, 2014)
BACKGROUND: Arsenic trioxide is effective in treating promyelocytic leukemia, and laboratory studies demonstrate that arsenic trioxide causes apoptosis of human breast cancer cells. Region II in northern Chile experienced very high concentrations of inorganic arsenic in drinking water, especially in the main city Antofagasta from 1958 until an arsenic removal plant was installed in 1970. METHODS: We investigated breast cancer mortality from 1950 to 2010 among women in Region II compared to Region V, which had low arsenic water concentrations. We conducted studies on human breast cancer cell lines and compared arsenic exposure in Antofagasta with concentrations inducing apoptosis in laboratory studies. FINDINGS: Before 1958, breast cancer mortality rates were similar, but in 1958–1970 the rates in Region II were half those in Region V (rate ratio RR = 0.51, 95% CI 0.40–0.66; p < 0.0001). Women under the age of 60 experienced a 70% reduction in breast cancer mortality during 1965–1970 (RR = 0.30, 0.17–0.54; p < 0.0001). Breast cancer cell culture studies showed apoptosis at arsenic concentrations close to those estimated to have occurred in people in Region II. INTERPRETATION: We found biologically plausible major reductions in breast cancer mortality during high exposure to inorganic arsenic in drinking water which could not be attributed to bias or confounding. We recommend clinical trial assessment of inorganic arsenic in the treatment of advanced breast cancer.